Effect of Planned Nursing Interventions on the Prevention of Acute Urinary Retention (AUR) in Male Patients after Cardiac Catheterization - Mahnaz khatiban; mohammadreza setvati basir; mohsen salavati; alireza soltanian (Hamadan University of Medical Sciences, 2017)
Introduction: With the increasing use of cardiac catheterization and its complications, such as urinary retention, finding a safe and non-invasive way to solve this problem is essential. The aim of this study was to evaluate the impact of planned nursing interventions on prevention of acute urinary retention in male patients, following cardiac catheterization, at educational and health centers of Hamadan city. Methods: In this interventional study, 74 patients with the study inclusion criteria and undergoing cardiac catheterization were selected by random sampling and were divided evenly to 2 intervention and control groups. Planned nursing interventions for the intervention group and routine nursing care for the control group was performed. The signs of incidence of acute urinary retention was investigated and compared in both groups at 0, 1, 2, 4, and 6 hours after the angiography procedure. Finally, the data was analyzed using by SPSS version 16 software. Results: According to the results, there was no significant difference between the intervention and control groups, regarding urinary retention at different times (P= 0.148). However, this difference was significant in the intervention group during specified times (P= 0.017). Conclusions: The results indicated the positive outcomes of planned nursing interventions in the prevention of acute urinary retention in patients following cardiac catheterization. This method could be used to prevent acute urinary retention in patients after coronary angiography